A study of medical practitioners' preference for print or electronic library materials - Villagracia, Ella S. (Institute of Library Science, University of the Philippines Diliman, 2002)
The study focused on the medical practitioner's preference for print and electronic library materials. It was conducted to: (1) determine the level of awareness of the medical practitioners in the UP College of Medicine on the electronic formats in publishing; (2) know which of the two formats they prefer; and (3) look into their information needs.